A comparison of Rasch with Likert scoring to discriminate between patients' evaluations of total hip replacement surgery. - Fitzpatrick, R; Norquist, J; Jenkinson, C; Reeves, B; Morris, R; Murray, D; Gregg, P (2004)
The purpose of this study was to examine whether there are advantages in terms of outcome assessment of using Rasch methods of scoring the 12-item Oxford Hip Score (OHS) questionnaire over conventionally Likert scores. As part of a prospective cohort study of total hip replacements in five former regions of England the OHS was sent to patients pre-operatively, at 3 months and 1 year post-operatively. Post-operative data was collected on over 5000 cases. Based on the level of satisfaction with surgery, patients were divided into satisfied and dissatisfied. Analyses were performed to test the relative precision (RP) of Rasch scoring vs. conventionally Likert scores in discriminating the groups experiencing different level of satisfaction. Considerable gains in precision were achieved with Rasch scoring methods when groups were compared 3 and 12 months post-operatively. The results from the current study suggest that in some situations there may be substantial gains in measuring health related outcomes using Rasch-based scoring methods.